Design and rationale of MYOFLAME-19 randomised controlled trial: MYOcardial protection to reduce post-COVID inFLAMmatory heart disease using cardiovascular magnetic resonance Endpoints - Valentina O. Puntmann; Dietrich Beitzke; Andreas Kammerlander; Inga Voges; Dominik D. Gabbert; Marcus Doerr; Bishwas Chamling; Biykem Bozkurt; Juan Carlos Kaski; Erica Spatz; Eva Herrmann; Gernot Rohde; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Cardiac symptoms due to postacute inflammatory cardiac involvement affect a broad segment of previously well people with only mild acute coronavirus disease 2019 (COVID-19) illness and without overt structural heart disease. Cardiovascular magnetic resonance (CMR) imaging can identify the underlying subclinical disease process, which is associated with chronic cardiac symptoms. Specific therapy directed at reducing postacute cardiac inflammatory involvement before development of myocardial injury and impairment is missing. Methods: Prospective multicenter randomized placebo-controlled study of myocardial protection therapy (combined immunosuppressive/antiremodeling) of low-dose prednisolone and losartan. Consecutive symptomatic individuals with a prior COVID-19 infection, no pre-existing significant comorbidities or structural heart disease, undergo standardized assessments with questionnaires, CMR imaging, and cardiopulmonary exercise testing (CPET). Eligible participants fulfilling the criteria of subclinical post-COVID inflammatory heart involvement on baseline CMR examination are randomized to treatment with either verum or placebo for a total of 16 weeks (W16). Participants and investigators remain blinded to the group allocation throughout the study duration. The primary efficacy endpoint is the absolute change of left ventricular ejection fraction to baseline at W16, measured by CMR, between the verum treatment and placebo group by absolute difference, using unpaired t-test confirmatively at a significance level of 0.05 significance level. Secondary endpoints include assessment of changes of symptoms, CMR parameters, and CPET after W16, and frequency of major adverse cardiac events after 1 year. Safety data will be analyzed for frequency, severity, and types of adverse events (AEs) for all treatment groups. The proportion of AEs related to the contrast agent gadobutrol will also be analyzed. A calculated sample size is a total of 280 participants (accounting for 22 subjects (8%) drop out), randomized in 1:1 fashion to 140 in the verum and 140 placebo groups. Conclusion: Myoflame-19 study will examine the efficacy of a myocardial protection therapy in symptomatic participants with post-COVID inflammatory cardiac involvement determined by CMR. The aim of the intervention is to reduce the symptoms and inflammatory myocardial injury, improve exercise tolerance, and preclude the development of cardiac impairment.